DETERMINAN MINAT BELI ULANG PADA RESTORAN BERSERTIFIKASI HALAL YANG DIMEDIASI KEPERCAYAAN - Sharmila; Umuri, Khairil; Farma, Junia (Universitas Negeri Surabaya, 2023)
The development of the halal industry is an advantage for the Indonesian state with a majority Muslim community. Restaurant is one of the businesses that is the main focus in the halal industry. This study empirically investigates the effect of price and service on repurchase intention at halal-certified restaurants. He also tries to explore the role of trust as a mediator in the relationship between price, service, and repurchase intention. A number of 85 customers of halal restaurants in Banda Aceh City were selected as research samples using a purposive sampling technique. This study uses primary data which is then analyzed using path analysis and the Sobel test. This study found that price and service have a significant effect on trust and repurchase intention. In addition, trust was found not to significantly mediate the effect of price on repurchase intention. On the other hand, trust was found to have a significant mediating effect on service on repurchase intention. It is hoped that halal restaurant entrepreneurs can improve service and adjust prices appropriately so that public trust increases so that repurchasing interest emerges. Entrepreneurs are also expected to maintain the halalness of their products.